2023
DOI: 10.1139/cjpp-2022-0534
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of liraglutide pretreatment on isoprenaline-induced myocardial injury in rats

Abstract: Type 2 diabetes mellitus (T2DM) increases the risk of cardiovascular disease, especially myocardial injury. Due to their hypoglycemic effects, glucagon-like peptide-1 receptor agonists (GLP-1RAs) are efficiently used for T2DM management. GLP-1RAs also have anti-inflammatory and antioxidative effects, and can improve cardiac function. The aim of this study was to investigate the cardioprotective effects of liraglutide, a GLP-1RA, on isoprenaline-induced myocardial injury in rats. The study included 4 groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…These findings align with our results, corroborating the protective effect of liraglutide against DCM reported in a previous study [27]. A significant reduction in the heart weight-to-body weight ratio observed in rats with diabetes that received liraglutide treatment-a pattern commonly observed in preclinical studies and clinical trials-further supports the cardioprotective effects of liraglutide [39][40][41].…”
Section: Discussionsupporting
confidence: 93%
“…These findings align with our results, corroborating the protective effect of liraglutide against DCM reported in a previous study [27]. A significant reduction in the heart weight-to-body weight ratio observed in rats with diabetes that received liraglutide treatment-a pattern commonly observed in preclinical studies and clinical trials-further supports the cardioprotective effects of liraglutide [39][40][41].…”
Section: Discussionsupporting
confidence: 93%
“…Liraglutide inhibited NADPH oxidase activity and increased the protein levels of SOD, CAT, and GPx. A recent study also showed that liraglutide-mitigated isoprenaline-induced myocardial injury in rats caused by a reduction in oxidative stress, improvement of CAT and SOD activity and markers of cardiac damage such as high-sensitivity troponin I, aspartate aminotransferase, alanine aminotransferase [ 49 ]. Moreover, GLP-1RAs appear to improve cardiac metabolism through enhanced glucose uptake, increased fatty acid oxidation, and improved mitochondrial function, contributing to better energy utilization and reduced oxidative stress in cardiac tissues [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The β 1 -adrenergic receptor (β 1 -AR) is involved in stress-induced cardiac injury [150]. GLP1R agonists protect the heart against the cardiotoxic effect of the β-AR agonist isoproterenol [151,152]. However, it is unknown whether GLP1R agonists protect the heart against stress-induced cardiac injury.…”
Section: Unresolved Issuesmentioning
confidence: 99%